The Influence of Geographical Origin, Age, Sex, and Animal Husbandry on the Spontaneous Histopathology of Laboratory Cynomolgus Macaques (Macaca Fascicularis): A Contemporary Global and Multisite Review of Historical Control Data. (July 2022) - Chamanza, Ronnie; Naylor, Stuart W.; Gregori, Michela; Boyle, Molly; Pereira Bacares, Marcia E.; Drevon-Gaillot, Elodie; Romeike, Annette; Courtney, Cynthia; Johnson, Kelsey; Turner, Julie; Swierzawski, Nadine; Sharma, Alok K.
To investigate the influence of geographical origin, age, and sex on toxicologically relevant spontaneous histopathology findings in cynomolgus macaques ( Macaca fascicularis ), we performed a comparative analysis of historical control data (HCD) from 13 test sites that included 3351 animals (1645 females and 1706 males) sourced from Mauritius, China, Vietnam, and Cambodia, aged from 2 to 9.5 years, and from 446 toxicology studies evaluated between 2016 and 2021. The most common findings were mononuclear infiltrates in the kidney, liver, brain, and lung, which showed highest incidences in Mauritian macaques, and heart, salivary glands, and gastrointestinal tract (GIT), which showed highest incidences of mononuclear infiltrates in mainland Asian macaques. Developmental and degenerative findings were more common in Mauritian macaques, while lymphoid hyperplasia and lung pigment showed higher incidences in Asian macaques. Various sex and age-related differences were also present. Despite origin-related differences, the similarities in the nature and distribution of background lesions indicate that macaques from all geographical regions are suitable for toxicity testing and show comparable lesion spectrum. However, in a toxicity study, it is strongly recommended to use animals from a single geographical origin and to follow published guidelines when using HCD to evaluate and interpretate commonly diagnosed spontaneous lesions.